2014 International Conference on Cyber-Enabled Distributed Computing and Knowledge Discovery 2014
DOI: 10.1109/cyberc.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

Attacking Random Keypads through Click Timing Analysis

Abstract: This paper introduces a new method for attacking Personal Identification Numbers(PINs) through analysis of time delay between clicks. While click timing attacks are not new, they previously relied on known spacings between keys. In our method, we do not focus on flaws or weaknesses in the system itself, but on the flaws inherent in the human aspect of the system. Our attack exploits unconscious patterns in PIN input that are a side-effect of the human memorization process to narrow the PIN down to a specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Almuairfi et al have pointed out that text-based password and PIN as two conventional alphanumeric methods that are too weak and prompt to speculation and dictionary attacks-that is, attackers can guess using some known patterns and higher-probability passwords [2][3] [27]. Similarly, Chiang and Chiasson also indicated that text-based passwords and PIN can suffer from brute force guessing attacks by which attackers try guess all possible password combinations especially when the length of the passwords is small [3].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Almuairfi et al have pointed out that text-based password and PIN as two conventional alphanumeric methods that are too weak and prompt to speculation and dictionary attacks-that is, attackers can guess using some known patterns and higher-probability passwords [2][3] [27]. Similarly, Chiang and Chiasson also indicated that text-based passwords and PIN can suffer from brute force guessing attacks by which attackers try guess all possible password combinations especially when the length of the passwords is small [3].…”
Section: Background and Related Workmentioning
confidence: 99%